L’informazione geografica protagonista a ITN 2010 - Lanza, Eliana; Sigot, Cristina (GEOmedia, 2010)
Geographic Information approaches ITN 2010 Turin is also confirmed for 2010 the most important location to discuss the present and the future of satellite navigation and mobile information. From Novembre 11 and 12 at the Lingotto Fiera in Turin will be held ITN - Infrastructure Telematics & Navigation, the European event can offer a complete and integrated picture of ITS (Intelligent Transport Systems) and mobility infrastructures.